Integration of digital health applications into the German healthcare system: development of “The DiGA-Care Path” - Giebel, G. D.; Abels, C.; Börchers, K.; Kampka, B.; Neusser, S.; Cissarek, H. R.; Plescher, F.; Wasem, J.; Blase, N. (Frontiers in Health Services, 2024)
Introduction Since 2019 people who have insured in the German statutory health insurance are entitled to use certified apps called the Digitale Gesundheitsanwendungen [Digital Health Applications (DiGAs)]. The prerequisite for this is that an app certified as DiGA and suitable for their diagnosis exists. The DiGA can then either be prescribed by a physician or psychotherapist or requested by the patient from the statutory health insurance fund. Given the novelty of this type of healthcare, the implementation of a DiGA should be closely monitored to identify potential weaknesses and achieve quality improvements. To enable an analysis of the supply of DiGAs step-by-step, we aimed to create the DiGA-Care Path. Methods We conducted three steps to create the DiGA-Care Path. First, a knowledge base was created based on a structured literature research matched with knowledge gathered from the superordinate research project “QuaSiApps” funded by the German Federal Joint Committee. Second, we aimed to create an “ideal-typical” DiGA-Care Path using a flowchart. Third, based on the first path, a final path was developed using the graphical modeling language “Event-Driven Process Chain.” Results The DiGA-Care Path was developed to depict the supply of DiGAs in Germany. The final path is constituted by a “main path” as well as a corresponding “sub-path”. While the “main path” focuses more on the supply environment in which a DiGA is used, the “sub-path” depicts the supply delivered by the DiGA itself. Besides the process itself, the paths include relevant actors to indicate responsibilities for individual process steps. Discussion The DiGA-Care Path helps to analyze the current supply of DiGAs step-by-step. Thereby, each step can be investigated in detail to identify problems and to detect further steps where quality improvements can be enabled. Depending on the perspective, focused either on the supply environment, or the supply delivered by the DiGA itself, the “main path” or the “sub-path” can be used, respectively. Besides the potential of the DiGA-Care Path to improve the current supply of DiGAs, it can help as an orientation for international policymakers or further stakeholders either to develop their own integration of apps into healthcare systems or for international manufacturers to consider entering the German market.